The Agency Theory Approach to the Public Procurement System - Chrisidu-Budnik, Agnieszka; Przedańska, Justyna (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
This paper combines elements of the agency theory with the practice of the public procurement system in Poland. It defines the concept of the agency relationship, shows its connection with the adverse selection and the moral hazard issue and investigates the nature of the agency generated by the existence of hidden information and hidden action. The main objective of the paper is to build and present a framework for analysing the mechanism of the agency theory in the public procurement system.
Keywords: teoria agencji; zamówienia publiczne